Analisis Pengaruh Kepemimpinan Abdi, Budaya Organisasi ,Perilaku Kewargaan Organisasi terhadap Kinerja Karyawan pada Institut Sains dan Teknologi Al Kamal - M. Zukrianto; Siagian, Arifin (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
The purpose of this study was to analyze the influence of leadership style of servant, organizational culture, and organizational citizenship behavior on employee performance at the Kamal Institute of Science and Technology, and to analyze the most dominant variables affecting employee performance at the Kamal Institute of Science and Technology. While the method of analysis used in this study is descriptive analysis, validity and reliability analysis, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results showed that the leadership of the servant, organizational culture and organizational citizenship behavior had positive and significant influence, while the leadership variable of the servant had a dominant inf luence in improving the performance of the employees at the Institute of Science and Technology Al Kamal, this is because with the leadership of the servants, it can motivate Employees and create a conducive working climate, so it can affect the improvement of employee performance, especially at the Institute of Science and Technology Al Kamal.